Coarctation: A Review - Marc G Cribbs (Radcliffe Medical Media, 2020)
Coarctation of the aorta occurs in 0.04% of the population, and accounts for approximately 10% of lesions in adults with congenital heart disease. It can occur as an isolated lesion or as a part of a complex defect, and is most commonly associated with bicuspid aortic valve, ventricular septal defect, and mitral valve abnormalities. Since the first surgical repair in 1944, the available treatment options have expanded greatly. Perhaps one of the most important advances in the management of coarctation of the aorta has been the development of transcatheter therapy for both native and especially recurrent coarctation of the aorta. Late complications, even after apparently successful treatment, are not uncommon. For this reason, lifelong follow-up is vital.